GREEN MARKETING STRATEGIES FOR A SUSTAINABLE BUSINESS - Velita, Lolita V; Suson, Jose R (Journal of Agriculture and Technology Management; Vol 23 No 1 (2020): Vol 23 No 1 (2020): Journal of Agriculture and Technology Management (JATM) Volume 23 January - June 2020 Issue, 2020)
Going green is becoming popular, which many are interested in because of several calamities and numerous ailments that people have experienced and encountered, specifically the most dreadful disease of the century; the Covid-19 pandemic drastically changes the consumer's buying behavior. However, only a few businesses practice it because of the absence of knowledge and information, which this study addresses.  Bohol Bee Farm, Daou, Dauis, Panglao, Bohol Philippines has a good business model to follow. It is a descriptive case study and purely qualitative. It used a structured open-ended interview guide, and the participants were the management of the company. Data were analyzed using SWOT Analysis and Thematic Analysis. The study revealed that the organization was able to segment, target, and position its products and services well and effectively practice its green marketing mix strategies, which increase business performance. The green marketing strategies, opportunities, and challenges found are the basis for proposed improvements of the existing system and development of the green marketing model worthy to benchmark for startups and budding entrepreneurs.